Capital structure and its determinants of listed Construction companies on hose - Tống, Thị Thủy Anh (2020)
This dissertation is a study on the capital structure in general its determinants of all listed companies operating in construction sector on HOSE in three years, from 2012 to 2014 in specific. It focuses on factors affecting capital structure including size, profitability, tangibility, growth opportunity, credit ratings, state ownership and Lag 1. After selecting, screening and using OLS regression model, the dissertation brings out statistical model that shows a clear trend in capital structure. At the same time, findings are analyzed and compared to the theoretical assumptions.